Phenomenology of being a safe taxi driver - Mahsa Mehri; Maryam Khazaee-Pool; Shirazeh Arghami (BMC, 2019)
Abstract Background In developing countries, a great number of people typically utilize public transportation such as Taxis. Therefore, taxi drivers have an important role in residents' well-being and safety. The aim of this study was to describe the subjective experiences and insights on safe driving among taxi drivers in Zanjan, Iran. Method In this qualitative study, 17 taxi drivers (23-54 years) were purposefully selected to participate in 11 semi-structured interviews, as well as one focus group (n = 6). The data was then analyzed based on a combination of Braun's and Colaizzi's methods. Result By analysis of the qualitative data, four main themes emerged from expressed experiences by taxi drivers, including 1) traffic chaos, 2) social prestige, 3) economic pressure, and 3) job satisfaction. Conclusion The emerging concepts of the present study imply a threefold structure of existence, which introduced by Heidegger, as taxi drivers' (the self) feelings and experiences of being under pressure of traffic chaos (the world), accompanied by low social prestige, economic pressure and job dissatisfaction (being in). Thus, strategic planning for traffic safety should consider taxi drivers' needs to feel a friendly world, as well as, to find themselves in a respectful and supportive environment.